Efficient three-color white organic light-emitting diodes with a spaced multilayer emitting structure - Yan, Fei (2015)
By employing a spaced multilayer structure in a uniformly mixed P and N co-host, we developed a three-color white organic light emitting device with a stable Commission Internationale de L'Eclairage coordinates insensitive to the applied bias voltage. This insensitivity was achieved by suppressing the exciton quenching and shifting recombination zone effectively. Besides the achieved stable color coordinates of (0.411 ± 0.007, 0.382 ± 0.003), a high power efficiency of 30.7 lm/W and high color rendering index >80 were realized simultaneously.